Systematic Literature Review of Syariah Regional Regulations Maqashid Syariah Perspective - Buhri, M. Nopri Ramadani Utama; Meilinda, Selvi Diana; Suwandi, Suwandi; Rozie , Azharisman (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
The primary substance of Sharia Regional Regulations (Perda) is to handle equality and injustice. In various areas such as Aceh, Pamekasan, and Medan, implementation gives rise to a view different from the party external. The difference creates disputes and leads to the conclusion that Sharia regulations are not the right solution for public multiculturalism. This study is about equality and injustice in Sharia Regional Regulations in Indonesia and its potential to handle the issue of humanity through the frame of Maqashid Al-Syariah. The research methods used​ are Systematic Literature Review (SLR) with software assistance such as Publish or Perish for secondary metadata search, Vosviewer for data visualization, and Brand24 for seeing the sentiment public about Sharia Regional Regulations in Indonesia. Research results show that polemic substance Sharia regulations in Indonesia are caused by sentiment negative who consider it a tool of intentional politics​. It was also found that contained articles​ in the Sharia regional regulations are correlated with objective main maqashid al-syariah Al- Kulliyatul Khamsah, that is, for protecting religion (Hifz Din), soul (Hifz Nafs), wealth (Hifz Mal), descendants (Hifz Nasl) and thoughts (Hifz Aql). Additionally, the method​ delivers comprehensive and analytical proof that existing Sharia regulations not only support Sharia but also support Sharia objectives such as justice, social welfare, and protection of the rights of individuals.